Pros and Cons of Nickel Mining in Raja Ampat: A Critical Discourse Analysis Based on Systemic Functional Linguistics (SFL) - Wahyuni, Dini Putriani; Sugaryamah, Deuis (Journal of English Language and Education, 2025)
Nickel mining in Raja Ampat, West Papua, has sparked intense debate among the government, corporations, indigenous communities, and environmental activists. This article analyzes the pro- and anti-mining discourse through the lens of Systemic Functional Linguistics (SFL), focusing on three language metafunctions: ideational, interpersonal, and textual. Data was extracted from a YouTube video transcript by Kompas TV (June 9, 2025), featuring perspectives from a minister, a parliament member, an activist, and a musician. The findings reveal how social actors construct reality, power relations, and legitimacy through linguistic choices, including modality, transitivity, and lexical cohesion. These findings highlight power dynamics and unequal access in environmental decision-making